Design and Development of Travel Assist, An App to Support Smart Tourism - Samsudin, Nooraida; Fahmy, Syahrul; Mohd Ali, Iliana; Wan Mohamed, Wan Ainul Alyani (International Journal of Integrated Engineering, 2022)
Tourism is the third largest contributor to Malaysia’s GDP, worth MYR 86.1 billion in 2019. It is expected that the number of tourists to Malaysia will reach 30 billion in 2020, translated to MYR 100 billion receipts. The Malaysian Smart Tourism 4.0 Initiative strives to unlock the full potential of the tourism industry through enabling technologies of IR 4.0. This work reports the results of an innovation project to support smart tourism in Malaysia. It entails the design and development of Travel Assist, a mobile App for visitors to Malaysia. Travel Assist integrates three common web services: Google Translate, Google Maps, and XE Converter, into one App. It was developed using MIT App Inventor and Adobe Dreamweaver, and suitable for iOS and Android 7.0 (Nougat) devices and above. The App was tested by a group of users to confirm its functionality and feasibility, and the validation results are encouraging. The underlying technology is robust enough to support future innovation ideas and services under the IR 4.0 umbrella.